2003
DOI: 10.1038/sj.bjc.6601181
|View full text |Cite
|
Sign up to set email alerts
|

Arginine deiminase: a potential inhibitor of angiogenesis and tumour growth

Abstract: Hydrolysis of plasma arginine to citrulline by arginine deiminase (ADI) was recently shown to suppress lipopolysaccharide-induced nitric oxide (NO) synthesis. Since arginine is the precursor of NO, and the latter modulates angiogenesis, we explored whether ADI treatment significantly affected tube-like (capillary) formation of human umbilical vein endothelial cells. Inhibition occurred in a dosedependent manner, both in the chorioallantoic membrane and the murine Matrigel plug assay. Inhibition of angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 33 publications
3
40
0
9
Order By: Relevance
“…Park et al also used HUVECs and recombinant ADI to show that ADI could inhibit angiogenesis in a dose dependent manner, and this inhibitory effect can be reversed by supplying arginine back to the culture medium [43]. Park et al also observed that recombinant ADI exerted inhibition of angiogenesis in their in vivo studies using chick embryo and mouse model [43]. This antiangiogenetic property of ADI suggested an effective way for treating tumors.…”
Section: Adi-peg20 Inhibits Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al also used HUVECs and recombinant ADI to show that ADI could inhibit angiogenesis in a dose dependent manner, and this inhibitory effect can be reversed by supplying arginine back to the culture medium [43]. Park et al also observed that recombinant ADI exerted inhibition of angiogenesis in their in vivo studies using chick embryo and mouse model [43]. This antiangiogenetic property of ADI suggested an effective way for treating tumors.…”
Section: Adi-peg20 Inhibits Angiogenesismentioning
confidence: 99%
“…Beloussow et al first [42] demonstrated the anti-angiogenic effect of recombinant ADI with cultured human umbilical vein endothelial cells (HUVEC). Park et al also used HUVECs and recombinant ADI to show that ADI could inhibit angiogenesis in a dose dependent manner, and this inhibitory effect can be reversed by supplying arginine back to the culture medium [43]. Park et al also observed that recombinant ADI exerted inhibition of angiogenesis in their in vivo studies using chick embryo and mouse model [43].…”
Section: Adi-peg20 Inhibits Angiogenesismentioning
confidence: 99%
“…В частности, установлено, что АД подавляет пролиферацию трансформированных клеток и оказывает противоопухолевое действие in vivo с минимальными побочными эффекта-ми [12,15]. Предполагают, что подавление роста опухолевых клеток происходит благодаря амино-кислотному голоданию из-за деплеции аргини-на и/или созданию дефицита метаболитов этой аминокислоты, таких как NO и полиамины [14,16]. Однако противоопухолевое действие фер-мента может быть обусловлено также его анти-ангиогенной активностью.…”
Section: Introductionunclassified
“…A comparative analysis of anti-proliferative activity of original S. pyogenes M49-16 strain and its isogenic mutant with arginine deiminase gene deletion (M49-16delAD) was performed, using an endothelial EA.hy926 cell line. The bacterial supernatantes obtained by sonication of S. pyogenes M49- 16 and M49-16delAD were tested. The ability of S. pyogenes M49-16 and M49-16delAD supernatantes to hydrolyze arginine was assessed.…”
Section: A Role Of Arginine Deiminase From Streptococcus Pyogenes M49mentioning
confidence: 99%
“…[2,6,11,16,23,27]. ADI has also been known to inhibit the growth of melanoma and hepatocellular carcinoma cells in vitro as well as in vivo [19,20,24,26]. This anti-tumor activity of ADI has been attributed to the depletion of L-arginine, which is essential in these tumor cells [20,25].…”
mentioning
confidence: 99%